2023
DOI: 10.3389/fonc.2023.1083285
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumour DNA as biomarker for rectal cancer: A systematic review and meta-analyses

Abstract: BackgroundCirculating tumour DNA (ctDNA) has been established as a promising (prognostic) biomarker with the potential to personalise treatment in cancer patients. The objective of this systematic review is to provide an overview of the current literature and the future perspectives of ctDNA in non-metastatic rectal cancer.MethodsA comprehensive search for studies published prior to the 4th of October 2022 was conducted in Embase, Medline, Cochrane, Google scholar, and Web of Science. Only peer-reviewed origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The current study found a hazard ratio for ctDNA presence after surgery in CRLM patients of 3.12 (95% CI 2.27-4.28) for recurrence and of 5.04 (95% CI 2.53-10.04) for overall survival. Faulkner et al reported similar hazard ratios for the overall survival in the primary colorectal cancer setting, in which more extensive ctDNA research has been conducted [30]. On the other hand, the hazard ratio for recurrence seems to be lower for colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The current study found a hazard ratio for ctDNA presence after surgery in CRLM patients of 3.12 (95% CI 2.27-4.28) for recurrence and of 5.04 (95% CI 2.53-10.04) for overall survival. Faulkner et al reported similar hazard ratios for the overall survival in the primary colorectal cancer setting, in which more extensive ctDNA research has been conducted [30]. On the other hand, the hazard ratio for recurrence seems to be lower for colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 83%
“…23-29.34), marking its importance in the primary setting [31]. Another recently published systematic review showed a progression-free survival with a hazard ratio of 7.93 (95% CI 4.27-14.75) in a subgroup meta-analysis of postoperative ctDNA following surgery for primary colorectal cancer, in favour of a postoperatively negative ctDNA status [30]. In the metastasised setting, this difference was still significant but to a lesser extent (HR 4.58, 95% CI 2.26-9.28).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with recurrent disease displayed a median level of 13,000 copies/mL, in contrast to the 5200 copies/mL observed in non-recurrent patients (p = 0.08). This investigation also established a correlation between the total cell-free DNA levels and both the pathological stage and nodal involvement [22].…”
Section: Discussionmentioning
confidence: 74%
“…In the ctDNA-guided arm, only 28% of patients were ctDNA-positive 4-7 weeks after TME, resulting in fewer patients treated with adjuvant chemotherapy compared with patients randomized to standard management. 79 In rectal cancer, a meta-analysis demonstrated that ctDNA analysis can be used to risk stratify patients for recurrence, specifically when detected after neoadjuvant therapy. 80 A prospective biomarker study of 154 rectal cancer patients reports detectable ctDNA in 77% prior to chemoradiation, 8.3% after chemoradiation, and 12% after surgery.…”
Section: Future Directionsmentioning
confidence: 99%